Spectrum of care approach to animal shelter management of feline infectious peritonitis complicated by feline leukemia virus - LaVigne, Emma K.; Levy, Nicole E.; Bardzinski, Alexis R.; Scaletti, Federica; Horecka, Kevin; Cuccinello, Mia K.; Moore, Dana M.; Levy, Julie K. (Frontiers in Veterinary Science, 2025)
IntroductionFeline infectious peritonitis (FIP) occurs most commonly in multi-cat environments such as animal shelters. FIP is often suspected based on compatible history, signalment, physical examination, and hematological and biochemical findings. Increased diagnostic certainty requires additional diagnostic imaging and laboratory testing that may be out of reach for resource-poor caregivers and organizations. The objective of this retrospective study was to evaluate response to GS-441524 (GS) therapy of cats diagnosed with FIP using a spectrum of care approach relying on physical examination, hematology, biochemistry, and Feline Leukemia Virus (FeLV) antigen at a shelter specializing in the adoption of cats with FeLV.MethodsThe FIP treatment protocol included treatment with GS for 84 days, followed by observation for 84 days. Starting dosage, dose adjustment, route of administration, and treatment extensions were based on initial condition and response to therapy. Hematology and biochemistry panels were performed at baseline, treatment, and post-treatment observation periods. Response to treatment and survival times were compared between FeLV-positive and FeLV-negative cats.ResultsA total of 170 cats diagnosed with FIP (104 FeLV-positive; 66 FeLV-negative) were included in the study. Hematology and serum chemistry abnormalities and their resolution during treatment were not significantly different between the groups, nor were there significant differences in survival through the treatment period (79% vs. 76%) or observation period (74% vs. 74%) between FeLV-positive and FeLV-negative cats respectively. Most mortality (55%) occurred in the first 7 days; cats surviving >7 days had an 86% survival rate. Despite equivalent responses to GS treatment, the FeLV-positive group experienced progressive mortality following the observation period. Survival of FeLV-positive cats (median 524 days, range 1-1585 days) was significantly shorter than for FeLV-negative cats (median not reached, range 0-1424 days) (p = 0.0001). Fifteen cats (11%) that achieved remission of FIP during the initial treatment experienced one or more episodes of FIP relapse up to 1.2 years later (11 FeLV-positive; 4 FeLV-negative).DiscussionThe spectrum of care diagnostic approach appeared to be sufficient and preserved resources for the successful treatment of shelter cats. FeLV-positive cats achieved equivalent FIP remission rates to FeLV-negative cats but were still at risk for shortened lifespan associated with FeLV infection.